2002
DOI: 10.1038/sj.bjc.6600628
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal radiosensitivity in breast cancer patients with a known or putative genetic predisposition

Abstract: The chromosomal radiosensitivity of breast cancer patients with a known or putative genetic predisposition was investigated and compared to a group of healthy women. The chromosomal radiosensitivity was assessed with the G2 and the G0-micronucleus assay. For the G2 assay lymphocytes were irradiated in vitro with a dose of 0.4 Gy 60 Co g-rays after 71 h incubation, and chromatid breaks were scored in 50 metaphases. For the micronucleus assay lymphocytes were exposed in vitro to 3.5 Gy 60 Co g-rays at a high dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
125
4
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(148 citation statements)
references
References 32 publications
18
125
4
1
Order By: Relevance
“…In a small study of nine individuals with germ-line BRCA1 mutations, Baria et al (2001) found that the micronucleus test (also referred to as the G 0 micronucleus test) was useful at discriminating between carriers and non-carriers. Similarly, Baeyens et al (2002) observed enhanced radiosensitivity among breast cancer patients with a BRCA1 or BRCA2 mutation, vs a control group of healthy women, with the micronucleus test but not the G 2 assay (number of chromatid breaks). It is interesting to note that for the micronucleus test, radiation was provided at both a low and high dose rate, and that enhanced sensitivity among women with a mutation was documented for the low dose rate (78 vs 33% for low and high dose rate, respectively).…”
Section: Discussionmentioning
confidence: 84%
“…In a small study of nine individuals with germ-line BRCA1 mutations, Baria et al (2001) found that the micronucleus test (also referred to as the G 0 micronucleus test) was useful at discriminating between carriers and non-carriers. Similarly, Baeyens et al (2002) observed enhanced radiosensitivity among breast cancer patients with a BRCA1 or BRCA2 mutation, vs a control group of healthy women, with the micronucleus test but not the G 2 assay (number of chromatid breaks). It is interesting to note that for the micronucleus test, radiation was provided at both a low and high dose rate, and that enhanced sensitivity among women with a mutation was documented for the low dose rate (78 vs 33% for low and high dose rate, respectively).…”
Section: Discussionmentioning
confidence: 84%
“…We hypothesise a possible role for genetic variants in DNA doublestrand break repair genes in this patient group, since a significant proportion of these patients showed elevated chromosomal radiosensitivity by in vitro assays (Baeyens et al, 2002).…”
Section: Discussionmentioning
confidence: 93%
“…Out of all BC patients, 2% have a strong genetic predisposition, caused by the highly penetrant BRCA1 and BRCA2 genes (Peto et al, 1999). Because these genes cannot account for the overall increased risk in the relatives of BC cases (Baeyens et al, 2002), it was suggested that a substantial proportion of BC patients may be predisposed to cancer through mutations in low penetrance genes (Teare et al, 1994;Roberts et al, 1999;Scott et al, 1999;Scott, 2004), which may be genes involved in DNA damage processing and repair.…”
mentioning
confidence: 99%
“…Apart from these rare syndromes, the deficient DNA repair capacity has been proposed to be a predisposing factor in familial BC and in some sporadic BC cases (Parshad et al, 1996). Genomic instability has also been described for various hereditary cancers including hereditary BC (Rothfuß et al, 2000;Baeyens et al, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation